Online Ordering Systems: Development of Order Calculation using a Web-Based Calculator - Muhammad Lutfy, Afiq Danis; binti Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2023)
Customers today seek efficiency and variety in their purchases; thus,restaurant and café online ordering systems are rapidly expanding. This is because an online ordering system will simplify the meal ordering process. However, we discovered that most online ordering platforms provide a system that is difficult for consumers to understand and use. Therefore, in this research, we developed an online ordering system that is simple to learn and use and may assist users in growing their businesses. The suggested system displays a user interface and updates the menu with all available options to make the customer's work easier. We also will develop a valuable database from their customer’s transactions that will provide crucial information to users for them to improve their business. We will concentrate on assisting small businesses that do not have an ordering system. We study Microsoft Excel features and visual basic analysis (VBA) code to develop a complete online ordering system. All relevant data will be stored in the database for analysis in graph form. The existence of the graph may assist the users in further growing their business. Finally, we will review the results based on system performance and examine the database that was saved into Microsoft Excel. In the future, we will focus on improving the design and adding security features to the Microsoft Excel workbook. Furthermore, we will improve the method this Microsoft Excel workbook is shared so that macro functions may be used.